2012
DOI: 10.1261/rna.029413.111
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of PNPase in the degradation of small RNAs that are not associated with Hfq

Abstract: The transient existence of small RNAs free of binding to the RNA chaperone Hfq is part of the normal dynamic lifecycle of a sRNA. Small RNAs are extremely labile when not associated with Hfq, but the mechanism by which Hfq stabilizes sRNAs has been elusive. In this work we have found that polynucleotide phosphorylase (PNPase) is the major factor involved in the rapid degradation of small RNAs, especially those that are free of binding to Hfq. The levels of MicA, GlmY, RyhB, and SgrS RNAs are drastically increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 71 publications
6
113
1
Order By: Relevance
“…The binding of sRNAs by Hfq protects them from degradation (Sledjeski et al 2001;Moller et al 2002;Andrade et al 2012;Fei et al 2015), but Hfq can also recruit the degradosome to sRNA-mRNA complexes, which leads to their accelerated decay (Ikeda et al 2011). Moreover, Hfq promotes the pairing of certain sRNAs to their mRNA targets (Moller et al 2002;Zhang et al 2002;Maki et al 2008;Soper and Woodson 2008), and facilitates the annealing of regulatory RNA-OUT to transposase-encoding RNA-IN (Ross et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of sRNAs by Hfq protects them from degradation (Sledjeski et al 2001;Moller et al 2002;Andrade et al 2012;Fei et al 2015), but Hfq can also recruit the degradosome to sRNA-mRNA complexes, which leads to their accelerated decay (Ikeda et al 2011). Moreover, Hfq promotes the pairing of certain sRNAs to their mRNA targets (Moller et al 2002;Zhang et al 2002;Maki et al 2008;Soper and Woodson 2008), and facilitates the annealing of regulatory RNA-OUT to transposase-encoding RNA-IN (Ross et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that the deletion of pnp, encoding the 3= to 5= phosphorolytic exoribonuclease polynucleotide phosphorylase (PNPase), paradoxically reduces the stability of several sRNAs, including CyaR and RyhB, during exponential growth (18,19). Deletion of pnp also resulted in the decreased regulation of mRNA targets by CyaR and other sRNAs (18,20).…”
mentioning
confidence: 99%
“…A pnp mutant accumulates numerous RNA fragments produced by endoribonucleic cleavages due to a major defect in poly (A)-dependent degradation (Braun et al 1996;Coburn and Mackie 1998). PNPase is involved in the turnover of sRNAs, the modulation of RNase II expression and in the processing of RliD-CRISPR in Listeria (Zilhao et al 1996;Andrade and Arraiano 2008;De Lay and Gottesman 2011;Andrade et al 2012;Sesto et al 2014). PNPase enzymatic activity is dependent on magnesium-chelated citrate, ATP and c-di-GMP, thereby creating a network between metabolism and RNA turnover (Del Favero et al 2008;Nurmohamed et al 2011;Tuckerman et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Its association with the RhlB helicase, another component of the degradosome, allows PNPase to disrupt very stable secondary structures that cannot be degraded by the free enzyme in E. coli (Régnier and Hajnsdorf 2009). PNPase degrades certain small RNAs (sRNA) (Andrade and Arraiano 2008;Andrade et al 2012), but it can also interact with sRNAs in a nondestructive mode together with Hfq in E. coli or in complex with Rsr protein in Deinococcus radiodurans, where Y RNA act as adaptors between the two proteins (Chen et al 2013;Bandyra et al 2016).…”
Section: Introductionmentioning
confidence: 99%